2004
DOI: 10.1016/j.cell.2004.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA Polymerase through the Secondary Channel

Abstract: High-resolution crystal structures have highlighted functionally important regions in multisubunit RNA polymerases, including the secondary channel, or pore, which is postulated to allow the diffusion of small molecules both into and out of the active center of the enzyme. Recent work from several groups has illustrated how regulatory factors and small molecules can exploit the secondary channel to gain access to the active site and modify the transcription properties of RNA polymerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…In particular, we consider the possibility of predicting pause positions where RNAP halts either reversibly (pauses) or irreversibly (arrests) (13). Pauses, which are characterized by highly variable durations and efficiencies (3), are an ubiquitous aspect of transcription elongation and are known to play regulatory roles particularly in synchronizing transcription with other biological processes, such as translation in bacteria (14), factor-dependent and factor-independent termination (15,16), and interactions with regulatory proteins (17). Even though pauses are not associated with a consensus sequence, pause positions along the template are strongly sequence-dependent.…”
mentioning
confidence: 99%
“…In particular, we consider the possibility of predicting pause positions where RNAP halts either reversibly (pauses) or irreversibly (arrests) (13). Pauses, which are characterized by highly variable durations and efficiencies (3), are an ubiquitous aspect of transcription elongation and are known to play regulatory roles particularly in synchronizing transcription with other biological processes, such as translation in bacteria (14), factor-dependent and factor-independent termination (15,16), and interactions with regulatory proteins (17). Even though pauses are not associated with a consensus sequence, pause positions along the template are strongly sequence-dependent.…”
mentioning
confidence: 99%
“…12). We suggest that detection of defects in regulation in ⌬dksA strains could potentially be compromised by compensatory effects of other DksA-like proteins, such as GreA and GreB, that can inhabit the secondary channel of RNAP (38,39) or by other compensatory mechanisms, especially given the extended time intervals inherent in steady-state assays. Fig.…”
Section: Effects Of Dksa On Positive Regulation Of Amino Acid Promotementioning
confidence: 99%
“…Escherichia coli possesses two highly homologous Gre factors: GreA and GreB. A structural study on the RNAP-GreB complex further revealed that CTD binds to the rim of the secondary channel of RNAP through which substrate nucleoside triphosphates for RNA synthesis enter the catalytic site (18,25,38), while NTD extends into the secondary channel and the tip reaches the catalytic center (28). Two acidic residues, D41 and E44, located at the tip of NTD, are conserved in Gre factors, including those of Bacillus subtilis, and are proposed to assist RNAP function by coordinating the Mg 2ϩ ion and water molecule required for catalysis of RNA hydrolysis (20,28,31).…”
mentioning
confidence: 99%